Livelihood adaptation to climate-related changes in agroecological zones in developing countries—challenges, prospects, and policy concerns - Hamer, Esan Ayeni; Oyedotun, Temitope D. Timothy; Charles, Elroy; Moonsammy, Stephan (Frontiers in Climate, 2025)
Climate change significantly threatens the livelihoods, biodiversity, and food security within agroecological zones (AEZs) of developing countries. This research presents a systematic review of peer-reviewed articles published between 2013 and 2023, highlighting facilitators and deterrents of effective livelihood adaptation strategies across AEZs within developing nations. The study identified two main thematic areas from these studies across several geographic regions: Challenges and Policies. These thematic areas were common across the AEZs, each with four primary subthematic areas. These subthemes highlighted insufficient stakeholder engagement, inconsistent policies, environmental harm or damage, and technological deficiencies. The review highlights the urgency of incorporating traditional participatory approaches and enhancing stakeholder harmonisation for robust policy formation. It emphasises the need for a tailored approach to adaptation strategies to address the distinct social, ecological, and governance structures of each unique AEZ according to its geographic characteristics. Finally, this review offers a new perspective on the complexity of climate change adaptation in AEZs, while establishing the foundation for future scholarly work and policy initiatives pertinent to enhancing resilience and coping mechanisms to climate change within AEZs of developing nations.